Scaling readiness: Accelerating the scaling of RTB interventions. Newsletter No.3 - Sartas, Murat; Schut, Marc; Pypers, Pieter; Schagen, Boudy van; Newby, Jonathan Craig; Velasco, C.; Thiele, Graham; Leeuwis, Cees (2017)
This is the third of the series of newsletters that will capture our efforts to develop an approach that will assess and accelerate the scaling of innovations in the CGIAR Research Program on Roots, Tubers and Bananas (RTB). This newsletter aims at introducing and giving visibility to the four case studies that are helping the Scaling Readiness team in developing and testing the tools and methods. In return, these projects are supported by the Scaling Readiness team to develop, implement and monitor strategies to support the scaling of innovations.